A silicon-on-insulator slab for topological valley transport - Xin-Tao He (Nature Portfolio, 2019)
Backscattering is one of the major factors that limit the performance of integrated nanophotonics. Here, He et al. realize topologically protected, robust and unidirectional coupling as well as optical transport on a silicon-on-insulator platform by exploiting the valley degree of freedom.